THE EFFECT OF CONCEPT ATTAINMENT LEARNING MODEL (CAM) TO X CLASS STUDENTS’ CRITICAL THINKING ABILITY - Ummi Hiras Habisukan; Munir .; Dini Afriansyah; Dewi Sundari (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
This research aims to determine whether the learning model Attainment Concept Model (CAM) effect against High School Students Critical Thinking Skills. This research uses quasi- experimental method with Pretest - Posttest Research Design Control Group Design . Sampling is done by saturated sampling technique. The sample of this research is X.1 dan X.2 class of science group study. The results showed that there are differences in critical thinking ability at animalia material. Improvement Critical thinking ability can be seen in the results before using learning model indicator that are Analysis, Evaluation, Inference (Conclusion), Explanation, Self regulation are 36%, 37%, 41 %, 45%, and 46 %. After using Learning Model on the indicator interpretation, analysis, evaluation, inference (conclusion), explanation, Self-regulation (setting themselves) are 80%, 84%, 85%, 85%, 83% and 84%. The results showed that learning model can enhance students critical thinking ability. The results of the statistics obtained tarithmetic = 3.474 and ttable = 1.666 with df (degrees of freedom) by 73 with a significant level of 5%, therefore tarithmetic > ttable is 3.474> 1.666 and 0.001 significance value> 0.05. Based on the hypothesis test, it can be concluded that the influence of learning model Concept Attainment Model on students’ critical thinking skills for X class. Keywords: animalia, Concept Attaiment Model (CAM), critical thinking, learning model